First Report of Crown Gall Caused by Agrobacterium rhizogenes on Korean Raspberry (Rubus crataegifolius) in Korea - Heeil Do; Hyeonheui Ham; Mi-Hyun Lee; Bang Wool Lee; Young Kee Lee (Research in Plant Disease)
In July 2022, the occurrence of crown gall was observed on Korean raspberry (Rubus crataegifolius) plants in a field in Gijang-gun, Busan, Korea. The galls appeared irregular in structure and varied in color from milky white to dark brown. The isolate formed round, mucoid, white colonies on yeast mannitol agar. The bacteria were gram-negative and appeared as short rods with multiple flagella. The physiological and biochemical characteristics of the isolate were consistent with those of Agrobacterium rhizogenes, and phylogenetic analysis classified the strain into the same group as A. rhizogenes. We confirmed the pathogenicity of the isolate by inoculating it into healthy Korean raspberry plants. Consequently, the causal agent of crown gall disease in the Korean raspberry was identified as A. rhizogenes. This study is the first to report crown gall disease caused by A. rhizogenes in Korean raspberry in Korea.